Plasma Human Cartilage Glycoprotein‐39 Is Associated With the Prognosis of Acute Ischemic Stroke - Xu, Tian; Zhang, Kaixin; Zhong, Chongke; Zhu, Zhengbao; Zheng, Xiaowei; Yang, Pinni; Che, Bizhong; Lu, Yaling; Zhang, Yonghong (Journal of the American Heart Association, 2022)
Background To evaluate the prognostic value of plasma YKL-40 (human cartilage glycoprotein-39) for acute ischemic stroke. Methods and Results We measured plasma YKL-40 levels in 3377 participants from CATIS (China Antihypertensive Trial in Acute Ischemic Stroke). Study outcome data on death, major disability (modified Rankin Scale score ≥3), and vascular diseases were collected at 3 months after stroke onset. The primary outcome was defined as a combination of death and major disability. During the 3-month follow-up, 828 participants (24.5%) experienced major disability or died. After multivariate adjustment, the highest YKL-40 quartile was associated with an increased risk of the primary outcome (odds ratio, 1.426 [95% CI, 1.105-1.839]; =0.01) compared with the lowest quartile. Each SD increase in log-transformed YKL-40 level was associated with a 15.5% (95% CI, 5.6-26.3%) increased risk of the primary outcome. The multivariable-adjusted spline regression models showed a linear dose-response relationship between YKL-40 and clinical outcomes. Adding YKL-40 to a model containing conventional risk factors significantly improved the reclassification power for the primary outcome (net reclassification improvement: 15.61%, <0.001; integrated discrimination index: 0.37%, =0.004) and marginally significantly improved the discriminatory power for the primary outcome (area under the receiver operating characteristic curve improved by 0.003, =0.099). Conclusions A higher YKL-40 level in the acute phase of ischemic stroke was associated with an increased risk of mortality and major disability at 3 months after stroke, indicating that YKL-40 may play an important role as a prognostic marker of ischemic stroke. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT01840072.